2009
DOI: 10.1002/pmic.200900022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two genetically related Entamoeba histolytica cell lines derived from the same isolate with different pathogenic properties

Abstract: Entamoeba histolytica is known for its extraordinary capacity to destroy human tissues, leading to invasive diseases such as ulcerative colitis or extra-intestinal abscesses. In order to identify the virulence factors of this parasite phenotypes and proteomes of two recently identified genetically related cell lines (A and B), derived from the laboratory E. histolytica isolate HM-1:IMSS, were compared. Both cell lines are indistinguishable on the basis of highly polymorphic tandem repeat DNA sequences. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 43 publications
0
54
0
Order By: Relevance
“…Recently, it was shown that CP activity of the pathogenic cell line HM-1:IMSS-B is approximately ten times greater (110 ± 25 mU/mg) than in the non-pathogenic cell line HM-1:IMSS-A (15 ± 5 mU/mg) [11]. A similar difference has been measured for the non-pathogenic clone A1 np (15 ± 10 mU/mg) and the pathogenic clone B2 p (123 ± 60 mU/mg) [3].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it was shown that CP activity of the pathogenic cell line HM-1:IMSS-B is approximately ten times greater (110 ± 25 mU/mg) than in the non-pathogenic cell line HM-1:IMSS-A (15 ± 5 mU/mg) [11]. A similar difference has been measured for the non-pathogenic clone A1 np (15 ± 10 mU/mg) and the pathogenic clone B2 p (123 ± 60 mU/mg) [3].…”
Section: Resultsmentioning
confidence: 99%
“…Whereas cell line HM-1:IMSS-A completely lost its ability to induce ALAs in gerbils ( Meriones unguiculatus ) and mice ( Mus musculus ), cell line HM-1:IMSS-B is highly aggressive and induces large ALAs. Comparative transcriptomic and proteomic studies of these cell lines have already been performed [11]. The studies revealed 31 differentially (≥3-fold) expressed genes [12] and 31 proteins with differential abundances in HM-1:IMSS-A and HM-1:IMSS-B [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two cell lines with identical patterns at six STRs derived from the most widely used E. histolytica HM-1:IMSS isolate showed two different virulence phenotypes: one was highly virulent in experimental animals while the other was not [ 42 ]. In a recent study in China, Feng et al [ 43 ] identifi ed two patients with different outcome of infections who were infected with the same genotype of E. histolytica .…”
Section: Other Limitations Of Trna Gene-linked Str Markersmentioning
confidence: 96%
“…There are characteristic molecules involved in the virulence of the parasite, such as cysteine proteases, pore-forming proteins and lectins, which allow various activities, such as phagocytosis and tissue invasion [3,4]. It has been demonstrated that the inhibition of gene expression using antisense sequences blocks the production of molecules that can decrease virulence-altering cytopathic or cytotoxic events or phagocytosis [5,6,7,8]. However, blocking these cellular factors does not completely inhibit the pathogenicity of the protozoan.…”
mentioning
confidence: 99%